Purpose And Concept Of Character Education In Islamic Perspective: A Comparative Study Of Imam Zarkasyi and Ahmad Dahlan Thoughts - Azizah, Yunita Noor; Dinihari, Anggie Nadia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
The purpose of this article is to describe the purpose and concept of character education in Islamic perspective according to Imam Zarkasyi and Ahmad Dahlan’s thought and to found the similarities between their views about character education. The research that authors conducted in this paper is qualitative approach which included of library research. Authors used content analysis and comparative study as analysis data, which is an analysis of content that focuses on the interpretation of a work that tries to offer epistemological assumptions. The research findings showed that (1) Imam Zarkasyi’s concept on character education was explained in Five Principles of Modern Boarding School (Panca Jiwa Pondok Modern) as follows: sincerity; simplicity; independent; Islamic Brotherhood (ukhuwah islamiyah); and free spirit (2) And the basic concept of character education according to Ahmad Dahlan is based on Islamic perspective has consists of three things, faith, knowledge and charity (3) Imam Zarkasyi and Ahmad Dahlan had some similarities in character education as follows: prioritize personality and character education, emphasized the need for moral development that can be maximized in the education system in boarding school and schools, aspired to develop children physically and spiritually based on Islamic guidance (Qur’an and Sunnah), used exemplary / modeling method in character education implementation.